Estudo cinético da decomposição térmica de nanocristais de celulose de caroço de manga, eucalipto e celofane - Henrique, Mariana Alves (2014)
The use of cellulose nanocrystals (CN) as a reinforcing agent for polymeric matrices has attracted considerable attention because the cellulose nanocrystal-based nanocomposites typically exhibit thermal, mechanical and superior barrier properties compared to the pure polymer or conventional composites and additionally provide environmental benefits. In order to use these to the CN as a reinforcing agent polymer matrix, the thermal stability of these crystals is a key factor in that they can be used as effective reinforcement materials, since the thermoplastic processing temperatures often exceeds 200°C. In this work CN were obtained from different sources, cellulose of purified mango seed (PMS), eucalyptus kraft pulp (PK) and cellophane (CELL) by acid hydrolysis with HCl and H2SO4. The chemical compositon of PMS, PK and CELL used in the hydrolysis were determined for the levels of -cellulose, hemicelluloses, holocellulose, lignin and ash All NC were characterized by elemental analysis (C,H,N,S), x - rays diffraction (XRD), atomic force microscopy ( AFM ) and thermogravimetry analysis ( TGA ) . Through thermogravimetric analysis kinectic study of thermal decomposition of the CN was carried out, it was possible to determine the conversion ( ) of the thermal decomposition of each sample of NCC under different heating rates of 5 , 10 , 20 and 40 ° C.min-1 . Through these data was possible to estimate the activation energy involved in the thermal decomposition process by applying kinetic method ASTM E 1641 , and the kinetic method of Kissinger .